Airway Clearance Techniques in Primary Ciliary Dyskinesia: A Systematic Review - Qian, Liling; Lam, Bonnie; Zheng, Tun; Russo, Daniela; Ma, Jinhui; Yao, Xiaomei (Puerto Rico Health Sciences Journal, 2024)
Objective: Primary ciliary dyskinesia (PCD) is a respiratory disorder that impairs mucociliary clearance, leading to decreased lung function. Conventional chest physiotherapy (CCP) is the traditional airway clearance technique (ACT) and is considered a standard treatment for PCD patients. This systematic review investigated whether device supported ACTs are better alternatives for improving lung function and/or quality of life in PCD, compared with CCP. Methods: The OVID Medline, PubMed, CINAHL, and Cochrane databases were searched. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed, and the Grading of Recommendations, Assessment, Development, and Evaluation approach was used to aggregate the data. This systematic review has been registered on the International Prospective Register of Systematic Reviews website. Results: Of the 389 citations that resulted from our literature search, 2 randomized crossover trials that included a total of 54 patients were analyzed. The certainty of the aggregated study evidence was very low. No difference was identified between device-supported ACTs and CCP in terms of forced vital capacity and forced expiratory volume in 1 second in PCD patients aged 6 to 20 years. Conclusion: Device-supported ACTs could be considered alternative treatment options to replace CCP. High quality research is required to confirm this result.